Risk Factors for Tobacco Susceptibility in an Orthodontic Population: An Exploratory Study - Jashinsky, Jared Michael (Am J Orthod Dentofacial Orthop, 2017)
INTRODUCTION: Tobacco use is related to increased periodontal disease, tooth loss, decreased success of orthodontic appliances, and may inhibit orthodontic tooth movement. Most smokers start during adolescence. As most cessation attempts fail, prevention appears necessary. METHODS: A cross-sectional sample of orthodontic patients reported hypothesized risk factors for smoking and susceptibility to tobacco use initiation. Exploratory analyses regressed susceptibility to tobacco initiation on each hypothesized predictor variable in a separate logistic model that included a standard set of covariates. RESULTS: Significant odds ratios (OR) were found for the presence of a smoker in the home (OR=2.168; 95% confidence interval (CI), 1.144–4.107), a friend having no-smoking rules in their home and car (OR=0.337; 95% CI, 0.128–0.886), having been offered a cigarette (OR=4.526; 95% CI, 1.190–17.207), and exposure to tobacco advertisements (OR=1.910; 95% CI, 1.044–3.496). CONCLUSIONS: Peer, family, and environmental factors appear to increase children’s susceptibility to smoking in orthodontic populations. Attention to such factors could help dental clinicians more effectively identify susceptible young patients in need of anti-smoking advice. Prospective and experimental studies are required to confirm the role dental clinicians might play in youth smoking prevention.